Association Between miR-148a and DNA Methylation Profile in Individuals Exposed to Lead (Pb) - Araújo, Marília Ladeira de (2021)
2018/24643-1 (São Paulo Research Foundation, FAPESP, Brazil), by the National Council for Scientific and Technological Development (Brazil) and by grant UID-BIM-00009-2020 (Foundation for Science and Technology, FCT, Portugal).